2022
DOI: 10.1039/d1rp00180a
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the role of scaffolds in problem-based learning (PBL) in an undergraduate chemistry laboratory

Abstract: The need for shifting the expository laboratory instruction style to inquiry-based approaches is widely acknowledged. Problem-based learning (PBL), one of the inquiry-based approaches, advocates students’ self-directed learning. The literature...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…It was observed that the students’ groups were able to arrive at the EDs with the help of the scaffolds. A detailed study on the role of all the scaffolds is presented in another paper by the same authors . Our analysis suggests that these scaffolds served the dual purpose of (a) helping students in formulating the ED of the complex PBL task and (b) practicing science skills.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…It was observed that the students’ groups were able to arrive at the EDs with the help of the scaffolds. A detailed study on the role of all the scaffolds is presented in another paper by the same authors . Our analysis suggests that these scaffolds served the dual purpose of (a) helping students in formulating the ED of the complex PBL task and (b) practicing science skills.…”
Section: Discussionsupporting
confidence: 86%
“…A rubric assessed the EDs for inclusion of parameters of analysis and treatment method, logical sequencing of the steps, the inclusion of concentration of chemicals, and tools of measurement for a maximum score of 28…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…They discuss the problem with the group that has been created. The students can play an active, critical thinking and can exchange ideas in solving problems (Khumsikiew et al, 2015;Varadarajan & Ladage, 2022).…”
Section: Students' Results On a Limited Trialmentioning
confidence: 99%
“…Vygotsky's contribution to our understanding of the learning process is best visualized by his Zone of Proximal Development, which is the space between what a student is already capable of doing independently and what that student could be capable of with help. Instructors provide the scaffolding, or support structures, which help the learner's development between those two spaces (Cole et al, 1978;Varadarajan & Ladage, 2022). The role of the instructor is to help the learner gain knowledge that will lead them through the Zone of Proximal Development to the next level of development (Smagorinsky, 2018).…”
Section: Piaget and Vygotskymentioning
confidence: 99%